National security of India and international law - Patel, Bimal N. (Leiden, The Netherlands ; Koninklijke Brill NV, 2020)
The work focusses on the examination of the current interna tional environment and new factors affecting the national security policy mak ing of India. It aims to review economic security, diplomacy, terrorism, conven tional warfare, military intervention, refugee management, defence strategies, etc. in the fast-changing international affairs.
Includes index.
Keywords: National security -- Law and legislation -- India; International law -- India